174k views
0 votes
(2r-13)-(-6r+4)
what is the answer​

User Desval
by
4.8k points

1 Answer

4 votes

Answer:

8 r - 17

Explanation:

Simplify the following:

(2 r - 13) - (4 - 6 r)

Factor 2 out of -6 r + 4:

2 r - 13 - 2 (2 - 3 r)

-2 (2 - 3 r) = 6 r - 4:

2 r - 13 + 6 r - 4

Grouping like terms, 2 r - 13 - 4 + 6 r = (2 r + 6 r) + (-13 - 4):

(2 r + 6 r) + (-13 - 4)

2 r + 6 r = 8 r:

8 r + (-13 - 4)

-13 - 4 = -(13 + 4):

8 r + -(13 + 4)

13 + 4 = 17:

Answer: 8 r - 17

User BuZz
by
5.0k points